Understanding the role of the PDE advisors: identity, space and place - Hibarino, Denise Akemi; Nodari, Janice Inês (BELT - Brazilian English Language Teaching Journal, 2018)
This paper aims at discussing the identity of English professors who are advisors in the Programa de Desenvolvimento Educacional from the state of Paraná and their perceptions regarding the aforementioned continuous teacher training program for basic education teachers. The qualitative-interpretive research (Bortoni-Ricardo, 2008) articulates contributions from Norton (1997; 2013) about identity and investment, with the notions of space and place provided by Tuan (2013). From interviews with the professors who are advisors in the program, it was possible to notice an awareness of the limitation of their agency, and a resulting discomfort from it. Such awareness impacts on the understanding of their identities and on their places as trainers who are in training as well.